Imperfect competition in firm-to-firm trade - Ayumu Ken Kikkawa; Glenn Magerman; Emmanuel Dhyne (National Bank of Belgium, 2019)
This paper studies the implications of imperfect competition in firm-to-firm trade. Using a dataset on all transactions between Belgian firms, we find that firms charge higher markups if they have higher input shares among their buyers. We interpret this as firms competing as oligopolies to supply inputs to each buyer and build a model in which they charge different markups to different buyers. We use the estimated model to quantify how distortionary firm-to-firm markups are. Reducing all markups in firm-to-firm trade by 20 percent increases welfare by around 7 percent, suggesting large distortions due to double marginalization. We then investigate how endogenous markups in firm-to-firm trade alter predictions of the transmission of shocks. In the counterfactual where we take a fall in import prices as the shock, we show that allowing for oligopolistic competition generates larger cost reductions for some firms, and attenuates these for others relative to a case with constant markups. We demonstrate that a measure capturing firms' positions in the production chain is a key metric in explaining this heterogeneity.
Keywords: F12; L13; L14; 330; Firm-to-firm networks; imperfect competition